The effects of participating in a community concert band on senior citizens' quality of life, mental and physical health. Issue 2 (1st August 2019) - Barbeau, Audrey-Kristel; Cossette, Isabelle
Music participation has been shown to have many positive effects on older adults, including on perceived health, mental well-being and social interactions. However, researchers have yet to explore the experience of older adults who are just starting their musical journey. This study's goal was to determine the extent to which participating in a community band had an impact on the quality of life (QoL), mental health and physical health of beginner musicians 60+ years old. The theoretical framework used for this project was the biopsychosocial model, which posits that health is influenced by the interactions between biological, psychological and social factors. Using a quasi-experimental design, the researchers followed eight participants over four months of music instruction and compared them to a control group of eight non-musicians. Interviews, questionnaires and physiological tests were carried out pre- and post-intervention. Results were analysed using the biopsychosocial model's factors and thematic analyses. Physically, subjects reported self-perceived improvements in breathing and physical endurance. Psychologically, benefits included increased well-being, cognitive stimulation, sense of purpose and identity, as well as overall enjoyment. Socially, positive outcomes identified were being part of a group, meeting new people, and keeping in touch or reconnecting with friends. Band members reported a high level of satisfaction, which is in keeping with findings from the literature. Further pedagogical considerations are discussed.